From Blessing to Coercion: Parental Authority in Choosing a Child Life Partner in Simpang Padang Perspective on Islamic Family Law - Muhammad Iran Simbolon; Risalan Basri Harahap; Nining Afriani (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
One of the conditions for the legality of marriage according to the law in Indonesia is the consent of the two prospective brides. Forced marriage is a form of deviation from this principle and can be categorized as a form of violence against children, one of which is through the practice of forced matchmaking. This study aims to analyze the understanding of parental authority in the selection of children's life partners in the community of Simpang Padang Village, Bathin Solapan District, and to examine its conformity with the provisions of Islamic law and positive law. This type of research is an empirical legal research with a qualitative approach conducted on natural conditions through in-depth interviews with parents, children, community leaders, and village officials, and supported by documentation studies of relevant laws and regulations. The results of the study show that based on Article 6 of Law Number 1 of 1974 concerning Marriage, parents do not have the authority to force their children to determine their life partner, but only play a role in providing advice and consent for the benefit of the child. However, empirically, most parents in Simpang Padang Village do not fully understand the legal basis and purpose of the authority, because they view parental consent in child marriage as more of a customary and traditional obligation than a legal mechanism to protect immature children physically and psychologically. From the perspective of Islamic law, the practice of forced marriage is contrary to the principles of willingness (ridha), justice, and protection of the welfare of children, so it is necessary to increase legal understanding and public awareness so that the implementation of marriage is in line with sharia values and the provisions of laws and regulations.